Constitutional embodiment of people with special needs A comparative study - Aud, Khaled Kadhem; Jallab, M. Muhammad Najm (The International and Political Journal, 2023)
The issue of the constitutional embodiment of people with special needs is one of the important topics. That is because disability has a great role for the disabled person, his family, and individuals in society in general. It makes this social group face great difficulty in bearing the burdens of life. And due to the increasing percentage of people with special needs globally, in the Arab world and locally, caring with them has increased. With the growth of human knowledge, the fertilization of experiences and the exchange of information among the countries of the world, most constitutions paid attention to this phenomenon, and interest in it evolved from one constitution to another, with the change of constitutional formulations, to ensure more rights for this important group in society. By adopting an analytical description based on the analysis of constitutional texts, and a comparative approach that compares the constitutional articles related to people with needs with similar ones in the constitutions of other countries, the research seeks to clarify the importance that the constitution attaches to this category of society. The research is divided into three chapters, the first of which deals with the concept of people with special needs, and the second deals with the development of legal interest in them. The third deals with the rights and privileges of this social segment in contemporary constitutions.